Growth and survival rate of Nandus nandus (Hamilton 1822) larvae on some selected supplemental feeds in cistern (Asian Journal of Medical and Biological Research, 2017)
The aim of the investigation was to determine the effect of different food on growth and survival of Nandus nandus larvae. The experiment was conducted for 20 days in twelve (12) cisterns (9× 6×2.5ft) to assess the effect of Zooplankton, Artemia, Tubifex and Brand Nursery Feed on growth and survival of N. nandus larvae in cistern condition. The growth of N. nandus larvae varied significantly (P